PARTISIPASI MASYARAKAT DALAM TAHAP PEMBANGUNAN DESA Studi Kasus Dana Desa Di Desa Praihambuli, Kecamatan Nggaha Ori Angu, Kabupaten Sumba Timur, Nusa Tenggara Timur - Handrianus Vianey Melin Wula, Aris Umbu Hina Pari (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2018)
Finding the issue of developing a village development strategy in the RegionalAutonomy era that is related to community participation in the implementation ofactivities, especially at the planning stage of the activity so that it is oriented towardsthe sustainable empowerment of the poor. Specific targets to be achieved in this studyare: in the village development stage, especially in participating and finding solutionsfor the community to participate based on willingness, ability, opportunity to beinvolved in a development process especially in village development.In this study the authors used a study analysis conducted with: qualitativedescriptive method. Data collection techniques used in this study were conductedthrough interviews, observation, and documentation studies. In analyzing the datacarried out through data reduction, data presentation and drawing conclusions. As forthe work plan proposed in this study are; (1) Improving the welfare of ruralcommunities and the quality of human life and poverty reduction through meeting basicneeds, developing village facilities and infrastructure, building local economicpotential, and sustainable use of natural and environmental resources; (2)Strengthening villages and their communities that prioritize community participation sothat they are in accordance with what is most needed by the community.